Revamping Nigeria’s Economy Through The Teaching Of Literature-In English (2017)
Causes and effects of global economic recession have been discussed by scholars from different perspectives in recent times. It was observed that Economy in Africa has not been growing well compared to developed continents in the world due to problems of underdevelopment occasioned by bad governance, and wide-spread corruption. Nigeria economy at present is undergoing a severe experience of an economic recession. Since some of the factors undermining development in Africa are also responsible for economy that slid into recession, the focus of this paper is to identify and discuss factors that are responsible for economic recession in Nigeria and explain how it can be tackled through the teaching of Literature-in- English in secondary schools. The writers are of the opinion that the inculcation of desirable societal virtues such as patriotism, honesty, dignity of labour, self-sacrifice through compulsory teaching of Literature in English will be in line with the federal government change mantra and help in revamping the nation’s economy that slid into recession